Nurses perceptions about advice given in the neonatal intensive care unit - Oliveira, Kezia de; Orlandi, Márcia Helena Freire; Marcon, Sônia Silva (Rev Rene, 2011)
This an exploratory descriptive study conducted in Maringá/PR/BR which aimed to identify the guidance offered to families of newborns in Neonatal Intensive Care Unit in perceptions of the nurses themselves. Data were collected from November to December/2009, with 16 nurses working in these units through self-applicable questionnaire consisting of open questions. The results show that nurses recognize that the guidelines are insufficient to meet the needs of families and aim to: reduce anxiety and stress, maintain safety and operation of the service; encourage the mother-child bond and support the family. They focus among other things on the functioning of the sector, regarding the routines and equipment developments in clinical and general condition of the newborn, procedures and nursing care, breastfeeding and emotional support to parents. Communication between nursing staff and family members is essential to have an effective and efficient care.